EVALUATION OF AGRICULTURAL-BASED POVERTY ALLEVIATION PROGRAM USING CIPP MODEL: A CASE STUDY OF READSI PROGRAM IN BONE BOLANGO REGENCY - Dai, Sulistianto Amin; Saleh, Choirul; Amin, Fadillah (Erudio Journal of Educational Innovation, 2026)
This study aims to evaluate the Rural Empowerment and Agricultural Development Scaling-up Initiative (READSI) program in Bone Bolango Regency using the CIPP (Context, Input, Process, Product) evaluation model. READSI is an agricultural-based poverty alleviation program funded by the International Fund for Agricultural Development (IFAD) through the Indonesian Ministry of Agriculture. The research employed a qualitative descriptive method through in-depth interviews, observation, and document analysis. The results indicate that: (1) Context evaluation identified key problems affecting farmers, including low production factors, unclear product pricing, limited access to capital, poor market literacy, weak financial literacy, and low human resources quality; (2) Input evaluation found that selected program activities — farmer group strengthening, field schools, agricultural inputs (saprodi) assistance, agricultural machinery, and basic infrastructure — were contextually relevant; (3) Process evaluation revealed that implementation used the Participatory Rural Appraisal (PRA) method with several challenges including low farmer participation, misuse of saprodi assistance, and difficulties in collecting mandatory 30% contributions for agricultural machinery; (4) Product evaluation showed mixed results — the 20% indicator for formal financial institution access was achieved (27%), while the targets for joint business (15.08%), formal business entities (0%), savings groups (73.02%), and good performance farmers (56%) remain unmet. The findings suggest the program needs enhanced monitoring and community trust-building strategies to improve outcomes.